Interpreting Consumer Motivations for Luxury Consumption: An Application of the Zaltman Metaphor Elicitation Technique - Gao, Shijing (2018)
Over the recent decades, the global luxury market has grown dramatically, and Chinese consumers account for more than a quarter share of the targeted consumers in the luxury market. Thus, luxury consumption has gained attention from the academic researchers and marketing practitioners. The literature on luxury consumption is mainly focused on the Western context, and the previous studies usually examined consumers’ motivations for luxury consumption by separating the internal influences (i.e. the self-concept) from the external influences (i.e. the cultural and social factors). However, it is not clear that how consumers perceive luxuries within the Eastern cultures and what are the differences between motivations of males and females for luxury consumption. Therefore, this paper explores the underlying motivations of consumers within the Chinese cultures by combining the internal influences and external influences.